How English domiciled graduate earnings vary with gender, institution attended, subject and socio-economic background - Jack Britton; Lorraine Dearden; Neil Shephard; Anna Vignoles (Institute for Fiscal Studies (IFS), 2016)
This paper uses tax and student loan administrative data to measure how the earnings of English graduates around 10 years into the labour market vary with gender, institution attended subject and socioeconomic background. The English system is competitive to enter, with some universities demanding very high entrance grades. Students specialise early, nominating their subject before they enter higher education (HE). We find subjects like Medicine, Economics, Law, Maths and Business deliver substantial premiums over typical graduates, while disappointingly, Creative Arts delivers earnings which are roughly typical of non-graduates. Considerable variation in earnings is observed across diff erent institutions. Much of this is explained by student background and subject mix. Based on a simple measure of parental income, we see that students from higher income families have median earnings which are around 25% more than those from lower income families. Once we control for institution attended and subject chosen this premium falls to around 10%.
Keywords: 330; Administrative data; Graduate earnings; Human capital; Labour earnings; Degree subject; Student loans